Similia/Dissimilia : Modes of Abstractions in Painting : Sculpture and Photography Today. - Crone, Rainer; Städtische Kunsthalle Düsseldorf; Columbia University, New York; Leo Castelli Gallery, New York; Sonnabend Gallery, New York (Düsseldorf : Städtische Kunsthalle Düsseldorf, 1987)
Amar, Joseph ; Artschwager, Richard ; Balth, Carel ; Beuys, Joseph ; Alighiero e Boetti ; Cemin, Saint Clair ; Chamberlain, John ; Clemente, Francesco ; Flavin, Dan ; Halley, Peter ; Herold, Georg ; Hesse, Eva ; Horn, Roni ; Johns, Jasper ; Judd, Donald ; etc.
Similia/Dissimilia : Modes of Abstractions in Painting : Sculpture and Photography Today / Abstraktionen in Malerei, Skulptur und Photographie heute, Städtische Kunsthalle Düsseldorf / Columbia University, New York / Leo Castelli Gallery, New York / Sonnabend Gallery, New York, 1987-1988
boek